Wood has specific base properties of thermal and combustion. Since being grew normally at marginal soil of mining area, sengon buto, waru and gmelina woods were objectified to investigate thermophisic aspect of their usage as substitution fuel in cement production. Examination based on species, ages and horizontal positions of those woods showed that mean of heating value in oven dry and air dry condition was 4.505 kkal/kg and 4.084 kkal/kg, respectively. Determination of wood substitution to or - Tekat DWI CAHYONO; Zahrial COTO; Fauzi FEBRIANTO (Departemen Hasil Hutan, IPB, 2008)
Wood has specific base properties of thermal and combustion. Since being grew normally at marginal soil of mining area, sengon buto, waru and gmelina woods were objectified to investigate thermophisic aspect of their usage as substitution fuel in cement production. Examination based on species, ages and horizontal positions of those woods showed that mean of heating value in oven dry and air dry condition was 4.505 kkal/kg and 4.084 kkal/kg, respectively. Determination of wood substitution to ordinary fuel was acquired by accumulating heating value with prediction value of plantation biomass potency; and enquiry for 850 ha mining area resulted that waru wood will contribute about 5,14% to coal total requisite per year, gmelina and sengon buto will contribute about 5,03% and 4,49%, respectively. Keywords: Wood, heating value, substitution fuel